Centralized and Decentralized Delivery of Transgender Health Care Services: A Systematic Review and a Global Expert Survey in 39 Countries - Koehler, Andreas; Strauss, Bernhard; Briken, Peer; Szuecs, Daria; Nieder, Timo O. (Frontiers in Endocrinology, 2021)
Introduction Transgender health care is delivered in both centralized (by one interdisciplinary institution) and decentralized settings (by different medical institutions spread over several locations). However, the health care delivery setting has not gained attention in research so far. Based on a systematic review and a global expert survey, we aim to investigate its role in transgender health care quality. Methods We performed two studies. In 2019, we systematically reviewed the literature published in databases (Cochrane, MEDLINE, EMBASE, Web of Science) from January 2000 to April 2019. Secondly, we conducted a cross-sectional global expert survey. To complete the evidence on the question of (de-)centralized delivery of transgender health care, we performed a grey literature search for additional information than the systematic review and the expert survey revealed. These analyses were conducted in 2020. Results Eleven articles met the inclusion criteria of the systematic review. 125 participants from 39 countries took part in the expert survey. With insights from the grey literature search, we found transgender health care in Europe was primarily delivered centralized. In most other countries, both centralized and decentralized delivery structures were present. Comprehensive care with medical standards and individual access to care were central topics associated with the different health care delivery settings. Discussion The setting in which transgender health care is delivered differs between countries and health systems and could influence different aspects of transgender health care quality. Consequently, it should gain significant attention in clinical practice and future health care research.